The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.15537/smj.2015.9.12081
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital adult cardiac arrests in a university hospital in central Saudi Arabia

Abstract: Objectives:To report the characteristics of adult out-of-hospital arrest patients and their outcomes in Riyadh, Saudi Arabia.Methods:This is a prospective descriptive study of out-of-hospital adult arrests incident transported to King Khalid University Hospital, Riyadh, Saudi Arabia between July 2012 and September 2013.Results:A total of 96 adult patients were enrolled in this study. Males represented 62.5% of the participants. The mean age of the study population was 58.9 years, and specifically 30.8 years fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 3 publications
4
47
0
Order By: Relevance
“…ey are also afraid to make a mistake particularly with no AED device available in their workplace [19]. Many studies explained that poor availability, adequacy, distribution of AED, and training might be major factors that stand behind the OHCA high mortality rate [5,6,14,21].…”
Section: Knowledge About Cpr and Aed Inmentioning
confidence: 99%
See 1 more Smart Citation
“…ey are also afraid to make a mistake particularly with no AED device available in their workplace [19]. Many studies explained that poor availability, adequacy, distribution of AED, and training might be major factors that stand behind the OHCA high mortality rate [5,6,14,21].…”
Section: Knowledge About Cpr and Aed Inmentioning
confidence: 99%
“…In Saudi Arabia, the cardiovascular disease mortality rate is 37% according to the World Health Organization (WHO) statistics [4]. A study conducted in Riyadh city in Saudi Arabia reported a high mortality rate of 95.8% among adult OHCA patients; this study reported that poor training of cardiopulmonary pulmonary resuscitation (CPR) and nonutilization of an automated external defibrillator (AED) might be the major factors that stand behind the OHCA high mortality rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…I read the article on out-of-hospital cardiac arrests (OHCA) in its entirety and with a great interest 1. Bin Salleeh et al1 original research on OHCA is an outstanding milestone since Conroy and Jolin’s research in late 1990’s 2.…”
mentioning
confidence: 99%
“…Bin Salleeh et al1 original research on OHCA is an outstanding milestone since Conroy and Jolin’s research in late 1990’s 2. The Bin Salleeh et al research should lead to a collaborative nationwide effort among Universities and tertiary level hospitals in publishing data related to OHCA and to address the paucity of OHCA prevalence report in the Middle East 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation